Foraging efficiencies and species' distributions : an explanation of the Hadeda ibis (Bostrychia hagedash) in relation to soil moisture - Duckworth, Greg (Department of Biological Sciences, 2017)
The influence of soil moisture on the foraging time needed to meet BMR (foraging efficiency) in hadedas was explored in Cape Town, South Africa. This was done by monitoring hadedas foraging and recording the prey items eaten successfully per minute on soils of different moisture. BMR was calculated using a published method and diet calorimetry was used to determine the amount of energy in their diet. Results indicate that hadedas are able to forage most efficiently at intermediate soil moistures (0.40 -0.80 cm³.cm-³) whilst at either low or high soil moisture they are less efficient.